A new class of "pincer" receptors – macrocyclic systems containing an incorporated amide group. Issue 1 (22nd December 2020) - Niedbała, Patryk; Jurczak, Janusz
Abstract: Herein we present the synthesis and association analysis of a new family of "pincer" receptors containing units of stable 26-membered tetraamidic macrocyclic scaffolds in their structures. These units, linked by aliphatic or aromatic chains, are capable of binding an anionic guest due to the presence of amide functions playing the role of hydrogen bond donating systems. Such neutral receptors show strong binding properties with respect to dicarboxylate anions. Despite the discovery that we observed a complexed, mixed binding model in all the systems tested, we can infer that the receptor region to which the guest chain is associated depends on the latter's length. Graphical abstract: